What's in it for me? Self-serving versus other-oriented framing in messages advocating use of prosocial peer-to-peer services. Issue 109 (January 2018) - Vaish, Rajan; Liao, Q. Vera; Bellotti, Victoria
Highlights: Senders generally prioritized other-oriented motives. Senders paid attention to the service in question when deciding how to motivate recipients to join it. Recipients were more attracted to click on messages emphasizing self-serving benefits. After recipients clicked the messages, effects of self versus other-framing messages depended on the nature of the service. Abstract: We present a study that investigates the effectiveness of self-serving versus other-oriented motivational framing of messages designed to persuade people to sign up for a prosocial peer-to-peer (P2P) service. As part of the study, volunteer message senders were incentivized to recruit people to sign up for one of three types of prosocial P2P services. Senders were given an option of choosing one of four pre-designed invitation messages to send to their contacts, two framed for self-serving motivations and two framed for other-oriented motivations. We found that recipients were more attracted to click on messages emphasizing self-serving benefits. This may not match the expectation of senders, who generally prioritized other-oriented motives for participating in prosocial P2P services. However, after recipients clicked the messages to investigate further, effects of self versus other-framing messages depended on the nature of the service. Our findings suggest that, even for prosocial services, messages offering self-serving motivations are more effective than altruistic ones on inspiring interests. But the overall persuasive effect on conversion may be more nuanced, where the persuasion context (service type) appears to be a critical moderator.